Manajemen Gangguan Tidur Pada Pasien Hemodialisa - Vera Septiana, (2021)
In chronic renal failure patients undergoing hemodialysis, it is important to remove the wastes of protein metabolism and correct fluid and electrolyte balance (Black and Hawks, 2014). Chronic disease is a disease that is quite high in health problems that reduce the quality of patient sleep (Terzi, Topbaş, & Ergül, 2019). The overall prevalence in Iran of low sleep quality in hemodialysis patients is 75.30% (Mirghaed, Sepehrian, Rakhshan, & Gorji, 2019).